GlaViWo – A 3D Virtual World for an Arabist - Ruzicka, Ronald; Cerny, Elisabeth (Proceedings of the Seminar for Arabian Studies, 2023)
The Austrian Academy of Sciences (AAS) has a long tradition of research on ancient South Arabia. The scholar Eduard Glaser (born in Bohemia, at that time in the Austrian Empire) collected a lot of material in Yemen during the 1880s and 1890s. His estate consists of artefacts, squeezes, diaries and other manuscripts, photographs, notes, books, and articles about this fascinating region of the Near East. An important part of this estate is now preserved at the AAS (where it was been dealt with in two earlier projects), while other artefacts are kept in collections scattered across over the world, making it extremely difficult for researchers in South Arabian epigraphy and architecture, ethnology, geography, linguistics, and history to gain a full picture of what Glaser has gathered. The new project “GlaViWo” seeks to collect all available information on Glaser, store it in a database, and present it in the most modern way available, namely in a 3D virtual museum which will be created dynamically depending on the users’ requests. The paper presents both the GlaViWo database system and research results that have been obtained by means of collecting and interlinking items of and about Glaser.